Anetoderma with positive Darier's sign - Rana Rafiei; Eftekhari Hojat; Arash Daryakar; Leila Yusefkhani; Behnam Rafiee (Our Dermatology Online, 2017)
Anetoderma describes a localized laxity of the skin due to dermal elastolysis. It can be either primary or secondary to an inflammatory dermatosis. Rarely secondary anetoderma has been associated with mastocytosis. We report a 16-year-old man, with multiple pouch like lesions (anetoderma) mostly on the face, neck and upper trunk which had positive Darier`s sign. Anetodermic lesions developed two years ago without preceding urticaria pigmentosa lesions. In skin biopsy perivascular mast cell and eosinophil infiltrations were observed.